The Development of Marxist Shakespearean Criticism in China - Zhang, Wei (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
Chinese Shakespearean criticism from Marxist perspectives is highly original in Chinese Shakespeare studies. Scholars such as Mao Dun, Yang Hui, Zhao Li, Fang Ping, Yang Zhouhan, Bian Zhilin, Meng Xianqiang, Sun Jiaxiu, Zhang Siyang and Wang Yuanhua adopt the basic principles and methods of Marxism to elaborate on Shakespeare’s works and have made great achievements. With ideas changed in different political climates, they have engaged in Shakespeare studies for over eight decades since the 1930s. At the beginning of the revolutionary age, they advocated revolutionary literature, followed Russian Shakespearean criticism from the Marxist perspective, and established the mode of class analysis and highlighted realism. Before and after the Cultural Revolution, they were concerned about class, reality and people. They also showed the “left-wing” inclination, taking literature as a tool to serve politics. Since the 1980s, they have been free from politics and entered the pure academic realm, analysing Shakespearean dramas with Marxist aesthetic theories and transforming from sociological criticism to literary criticism.